2018
DOI: 10.1038/s41598-018-32745-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Tumor Heterogeneity on 18F-FDG PET/CT in HR+HER2− Metastatic Breast Cancer Patients receiving 500 mg Fulvestrant: a retrospective study

Abstract: Heterogeneity has been demonstrated to be a predictor of treatment failure and drug resistance. Our study aimed to investigate imaging parameters, including tumor heterogeneity, as prognostic factors of response to 500 mg fulvestrant using 18F-FDG PET/CT. Twenty-seven estrogen receptor (HR)-positive/HER2-negative metastatic breast cancer patients who received 500 mg fulvestrant and underwent 18F-FDG PET/CT before treatment were retrospectively included. In PET/CT scans, conventional parameters (maximum and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 21 publications
1
21
3
Order By: Relevance
“…However, SUVmax was found to be associated with patients' overall survival in other studies on breast cancer patients with distant metastasis [8,9,18,19]. It has also been reported that MTV and TLG were not predictive of patients' overall survival [18], which stands in contrast to our results.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, SUVmax was found to be associated with patients' overall survival in other studies on breast cancer patients with distant metastasis [8,9,18,19]. It has also been reported that MTV and TLG were not predictive of patients' overall survival [18], which stands in contrast to our results.…”
Section: Discussioncontrasting
confidence: 99%
“…However, SUVmax was found to be associated with patients' overall survival in other studies on breast cancer patients with distant metastasis [8,9,18,19]. It has also been reported that MTV and TLG were not predictive of patients' overall survival [18], which stands in contrast to our results. One reason could be the long follow-up time of our study (approximately 29 months) compared to previous studies with follow-up times of 15.6 [18], 26.6 [8], and 22.3 months [9].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…80 lesions were segmented and the following parameters assessed: SUVmean, SUVstd, SUVmax, COV, TLRE, Entropy log10, Entropy log 2, Volume, Homogeneity. These features were selected based on prior studies showing their predictive value with regards to treatment response and histopathology [41][42][43][44][45].…”
Section: Treatment-related Changes In Pet Parametersmentioning
confidence: 99%